Pengaruh Keterampilan Mengajar Guru Terhadap Hasil Belajar Siswa Kelas XI Program Keahlian Akuntansi di SMK Negeri 6 Makassar - Sri Dayanti; Sahade Sahade; Fajriani Azis Azis (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2023)
: This study was intended to assess how influential the teaching skills of teachers on the learning outcomes of students in Class XI accounting SMK Negeri 6 Makassar. teacher teaching skills and learning outcomes as independent and dependent variables in this study. This study involved Every Student of Class XI AK 1 and XI AK 2 in SMK Negeri 6 Makassar. Population samples were taken from the entire core population and a sample of 66 students using saturated sampling techniques. As a method for collecting data, questionnaires and documentation. Among the data analysis methods used are percentage descriptive analysis, instrument test, and hypothesis test. Based on the findings of a simple linear regression analysis of teacher teaching skills, calculated Y = 58.229 + 0.381 X, or learning outcomes of 0.381 units. While the product moment correlation test is included in the strong category with a correlation value (r) of 0.757, this shows that accounting class XI students learn more effective teachers in teaching. Analysis of the coefficient of determination (R2) produces a value of (R2) = 0.573 or 57 percent, while the remaining 43 percent due to other things. A significant value of 0.000 was found by T-test analysis.